(untitled) (Innovative professional education, 2022)
Information and technological culture of teachers in agricultural colleges simultaneously contains both components of professional and pedagogical culture and of general information culture. It is shown that the information competencies of the teacher are rationally formed and developed with the help of electronic training courses. The peculiarities of the development of information and technological culture of college teachers with the use of electronic training courses are substantiated.